Plant regeneration via direct somatic embryogenesis from leaf explants of Tolumnia Louise Elmore ‘Elsa’ - Shen, Hui-Ju; Chen, Jen-Tsung; Chung, Hsiao-Hang; Chang, Wei-Chin (Botanical studies, 2018)
Background Tolumnia genus (equitant Oncidium ) is a group of small orchids with vivid flower color. Thousands of hybrids have been registered on Royal Horticulture Society and showed great potential for ornamental plant market. The aim of this study is to establish an efficient method for in vitro propagation. Results Leaf explants taken from in vitro-grown plants were used to induce direct somatic embryogenesis on a modified 1/2 MS medium supplemented with five kinds of cytokinins, 2iP, BA, kinetin, TDZ and zeatin at 0.3, 1 and 3 mg l −1 in darkness. TDZ at 3 mg l −1 gave the highest percentage of explants with somatic globular embryos after 90 days of culture. It was found that 2,4-D and light regime highly retarded direct somatic embryogenesis and showed 95–100% of explant browning. Histological observations revealed that the leaf cells divided into meristematic cells firstly, followed by somatic proembryos, and then somatic globular embryos. Eventually, somatic embryos developed a bipolar structure with the shoot apical meristem and the root meristem. Scanning electron microscopy observations showed that the direct somatic embryogenesis from leaf explants was asynchronously. The somatic embryos were found on the leaf tip, the adaxial surface and also the mesophyll through a cleft, and it reflected the heterogeneity of the explant. The 90-day-old globular embryos were detached from the parent explants and transferred onto a hormone-free 1/2 MS medium in light condition for about 1 month to obtain 1-cm-height plantlets. After another 3 months for growth, the plantlets were potted with Sphagnum moss and were acclimatized in a shaded greenhouse. After 1 month of culture, the survival rate was 100%. Conclusions In this report, a protocol for efficient regenerating a Tolumnia orchid, Louise Elmore ‘Elsa’, was established via direct somatic embryogenesis and might reveal an alternative approach for mass propagation of Tolumnia genus in orchid industry.